Photographic Image as a Key Element of Contemporary Advertisement - Kotsev, Angel (Sledva : NBU Journal of Humanities and Arts, 2020)
This article explores the general content of printed advertisement, its elements and their interaction. By making a brief presentation of the different elements involved in print advertising, the research attempts at presenting and summarizing the role in advertising of illustrations and photographic images in particular. The study will also try to give a clear answer to the question concerning the quantity of photographic images compared to other types of illustrations, drawings, collages or computer generated images in Bulgarian print advertising during the period 2000-2017.